Priority Analysis of Maternal and Child Health Problems in Majalengka Regency in 2024 - Nofitri, Refani Veralda; Khasanah, Lina; Karmanto, Bambang; Mohammad, Maula Ismail (LPPM Universitas Dhyana Pura, 2026)
The achievement of Sustainable Development Goals (SDGs) Targets 3.1 and 3.2 requires a responsive health system capable of accurately detecting and mapping maternal and child health issues. Indonesia continues to face major challenges, including high maternal mortality rates, stagnant progress in reducing stunting, and the burden of diseases that directly affect the well-being of mothers and infants. In 2020, Majalengka Regency ranked 7th highest in West Java in terms of infant mortality, with an IMR of 14.5 per 1,000 live births. This study aims to provide an overview of the conditions of maternal and child health problems using the PAHO Adapted Hanlon prioritization method in Majalengka Regency. The study employed a quantitative descriptive design to identify priority problems. The population consisted of all ten officers at the Majalengka District Health Office who were responsible for family health and nutrition programs. The sampling technique used was Total Sampling. Data was collected using a research instrument in the form of scoring sheets. Based on calculations using the PAHO Adapted Hanlon method, the priority order for maternal and child health issues is: 1) Chronic Energy Deficiency in pregnant women, 2) Stunting, 3) Low Birth Weight, 4) Anemia in pregnant women, 5) Infant mortality, and 6) Maternal mortality. The main priority for maternal and child health issues in Majalengka Regency in 2024 is pregnant women with Chronic Energy Deficiency. The consistent increase in the number of cases and the high level of severity necessitate focused mitigation efforts and effective interventions from the relevant health authorities.